Cooling Characteristics of Car Cabin Based on Thermal Evaluation Models - Wu Qingqing; Liu Jianhua; Zhang Liang; Zhang Jiawen; Jiang Linlin (Zhileng xuebao)
An experimental study is conducted to analyze the thermal environment and thermal comfort under the refrigeration conditions of the vehicle cabin. The experimental conditions are as follows. The air conditioning modes are refrigeration with indoor set temperature 26 ℃, automatic mode with internal circulation. The driving states are idle condition and road test. The experimental results show that the vehicle cabin temperature is affected by the spatial position and driving state. The uniformity of the temperature in the road test is higher than that in the idle condition. The humidity distribution of the vehicle cabin is also affected by the spatial position and driving state. The relative humidity difference between the front and rear on the road test is less than that of the idle condition. The temperature of the seat is affected by solar radiation and the occupant. The seat temperature is slightly higher than that of indoor air in the warming period and the cooling rate of the seat is much less than that of indoor air in the cooling period. The predicted mean vote (PMV) and the equivalent temperature models are basically consistent with the change of actual thermal comfort under the idle condition and road test. The prediction accuracy of the two models in the idle condition is higher than that on the corresponding road test. The overall prediction accuracy of the equivalent temperature model is higher than that of the PMV model.